Bi2SiO5@g-SiO2 upconverting nanoparticles: a bismuth-driven core–shell self-assembly mechanism. Issue 2 (19th December 2018) - Back, Michele; Trave, Enrico; Zaccariello, Gloria; Cristofori, Davide; Canton, Patrizia; Benedetti, Alvise; Riello, Pietro
Abstract : The low melting point of bismuth allows the fabrication of a lanthanide-doped Bi2 SiO5 crystalline-core/glassy silica-shell system through a simple impregnation of MSNs followed by thermal treatment. The synthetic strategy could be used for the synthesis of a wide variety of bismuth-based nanosystems. Abstract : Core–shell systems have attracted increasing interest among the research community in recent years due to their unique properties and structural features, and the development of new synthetic strategies is still a challenge. In this work, we have investigated lanthanide-doped Bi2 SiO5 nanocrystal formation inside mesoporous silica nanoparticles (MSNs). The role of both synthesis temperature and concentration of the bismuth precursor impregnated into the MSNs is discussed, showing an unprecedented strategy for the simultaneous stabilization of a crystalline core and a glassy shell. Temperature dependent synchrotron radiation X-ray powder diffraction (SR-XRPD) and high resolution transmission electron microscopy (HR-TEM) analyses allow one to follow the crystalline core growth. A mechanism for the formation of a Bi2 SiO5 @g-SiO2 core–shell nanosystem is proposed. In addition, the easy tunability of the color output of the upconverting system is demonstrated by means of suitable doping lanthanide ions with potential applications in several fields.